Effect of moist environment on the oxidation behavior of Mo76-xSi14B10Fex (x = 0, 0.5, 1 at.%) ultrafine composites in the range of 700–800 °C. (15th July 2019) - Kumar, N.K.; Mitra, R.; Das, J.
Highlights: Oxidation behaviour of Mo76- x Si14 B10 Fe x at 700–800 °C has been studied. Moist air improves the mass loss by 99% during isothermal oxidation. Fe addition improves the oxidation resistance in both dry and moist air. Abstract: The effect of moist environment on the isothermal oxidation behavior of Mo76- x Si14 B10 Fe x ( x  = 0, 0.5, 1 at .%) ultrafine composites containing proeutectic α–Mo solid solution phase and eutectic mixture of Mo3 Si (A15) and Mo5 SiB2 (T2) phases, have been investigated at temperatures in the range of 700–800 °C. The mass loss has been greatly improved by 99% in moist environment than that of dry air both at 700 °C and 800 °C. The addition of Fe further improves the oxidation resistance in both dry and moist air up to 24 h exposure. The x–ray diffraction and the scanning electron microscopic studies have been performed to reveal the evolution of different phases in the oxide scale and to explore the mechanism of oxidation. The cross-sectional area of the residue alloy in the oxidized coupons has been measured to be 98% in moist air for x = 1 and 50% in dry air for x = 0 than that of the initial alloy coupon pointing that the oxidation resistance of MoSiB can be greatly improved in presence of moist air as well as upon Fe addition.